Color particle slurry, particle glaze ceramic tile with three-dimensional decorative effect and preparation method thereof
By using color particle slurry containing the second transparent glaze, inorganic color material and specific organic binder, combined with bell cover glaze technology, the problem that ceramic tile decoration technology cannot achieve three-dimensional decoration effect is solved, the three-dimensionalization of ceramic decoration and the high-definition of patterns are achieved, and the stain resistance of the product is improved.
Patent Information
- Application Number
- CN202411886003.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The existing ceramic tile decoration technology cannot achieve three-dimensional decoration effect, and the multi-color printing and pattern updates are complex, resulting in high production costs and increased product scrapping rate.
A color particle slurry containing a second transparent glaze, an inorganic color material and a specific organic binder is used to form a three-dimensional decorative effect on the ceramic surface through bell glaze technology, and color particles are graded through specific proportions and processes to ensure the three-dimensional effect and stain resistance of the glaze layer.
The three-dimensional effect of ceramic decorative effects and the high-definition of pattern texture are achieved, avoiding the "slit" phenomenon during glaze coating, and improving the stain resistance and three-dimensional sense of ceramic products.
Smart Images

Figure CN119330594B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of ceramic technology, and in particular to a color particle slurry, a particle glaze ceramic tile with a three-dimensional decorative effect, and a preparation method thereof. Background Art
[0002] At present, the technical means of pattern decoration of ceramic tiles are relatively mature, and the more common means of industrial production are screen printing, roller printing and inkjet printing.
[0003] Screen printing is a technology that uses a screen printing plate to print. It uses the basic principle that the mesh holes of the graphic part of the screen printing plate are permeable to ink, while the mesh holes of the non-graphic part are not permeable to ink. In the surface decoration of ceramics, screen printing technology can print various patterns, texts, etc. on ceramic products to form a colorful decorative effect. However, screen printing can usually only print one color at a time. If multi-color printing is required, color registration is required. Color registration has high technical requirements, and it is difficult to ensure that the positions of each print are completely overlapped. It is easy to have inaccurate color registration, which increases the scrap rate of products and thus increases production costs.
[0004] Roller printing technology is developed on the basis of flat screen printing. It transforms the single intermittent printing of flat screen into continuous printing. The roller printing machine uses a special rubber roller made of a flexible and wear-resistant silicone. The designer inputs the designed pattern file into the computer, and the corresponding micropores are engraved on the surface of the rubber roller by the computer-controlled laser to form a printed pattern. During the printing process, the roller rotates and contacts the ceramic surface, and the ink is transferred to the ceramic through pressure to form a decorative pattern. However, once the pattern on the roller is engraved, it is more complicated and expensive to change, and the roller needs to be remade. Although the ceramic tile roller printing process has the advantages of high production efficiency and fine patterns, it also has disadvantages such as high equipment cost, long roller production cycle, high technical threshold, limited material adaptability, complex pattern update, and easy printing defects.
[0005] Inkjet printing technology is an advanced ceramic decoration method. It combines computer technology, inkjet printing technology and special ceramic color glaze technology. Through non-contact printing, it realizes efficient and high-quality decoration of ceramic surfaces. The working principle of inkjet printing technology is similar to that of an inkjet printer. Ceramic ink droplets are ejected from a nozzle with a diameter of tens of microns and rapidly deposited on the surface of the ceramic body at a rate of thousands of drops per second. These ink droplets form the desired pattern or texture on the ceramic surface and are fixed after high-temperature firing to form a permanent decorative effect. Any printed pattern can be efficiently switched according to the computer design file. Although ceramic inkjet printing technology has been able to achieve relatively rich color output, compared with traditional printing technologies such as screen printing and roller printing, its color saturation and vividness still have a lot of room for improvement, which is mainly limited by factors such as ink formulation, nozzle technology and printing equipment performance. In addition, the current ceramic inkjet printed patterns still have the problem of less than ideal pattern clarity. This is related to a series of factors such as the imperfect computer program control equipment for inkjet printing, the insufficient speed and direction smoothness of the conveyor belt, the printer nozzle, the ink supply system, and also related to the physical and chemical properties of the ceramic ink itself.
[0006] The common problem of screen printing, roller printing and inkjet printing is that they are surface decorations and cannot achieve three-dimensional decorative effects. For example, the existing production of glazed tiles or antique tiles for ceramic tiles prepares decorative patterns on the surface of the base glaze, and then covers the surface of the decorative patterns with glaze or antique glaze. Due to the flat decorative patterns, ceramic tiles are seriously lacking in three-dimensional sense compared with natural stones. Even if multiple processes are superimposed now, it is difficult to match the three-dimensional decorative effect of natural stones. Summary of the invention
[0007] Based on the defects of the prior art, the purpose of this application is to provide a color particle slurry, a particle glaze ceramic tile with a three-dimensional decorative effect and a preparation method thereof, so as to achieve the three-dimensional ceramic decorative effect and the high definition of the pattern texture.
[0008] In order to achieve the above-mentioned object, in a first aspect, the present application provides a color particle slurry, including a first transparent glaze, color particles and water;
[0009] The color particles include a second transparent glaze, an inorganic color material and an organic binder, wherein the weight ratio of the second transparent glaze to the inorganic color material is (15~75):(25~85), the weight of the organic binder is 10%~20% of the total weight of the second transparent glaze and the inorganic color material, and the organic binder includes at least one of dimethyl silicone oil, isopentyl acetate, and methyl benzoate.
[0010] The color particle slurry contains a first transparent glaze and color particles, and the glaze layer formed by it is based on transparent glaze, and the color particles are dispersed in the matrix, thereby presenting a three-dimensional effect. If the color particles are directly formed with inorganic color materials, that is, the color particles do not contain the second transparent glaze, since the inorganic color material is a high-temperature resistant material, in order to ensure color development, it will not melt and produce a liquid phase, resulting in poor adaptability to the first transparent glaze, and the location area where the inorganic color particles exist in the glaze layer has a loose structure and poor stain resistance. The present application adds an appropriate amount of the second transparent glaze to the color particles, which can not only effectively improve its adaptability to the first transparent glaze, but also make the location area where the inorganic color particles exist in the glaze layer dense, ensuring that the ceramic product has good stain resistance, and can also preserve the size of the color particles well to ensure a three-dimensional effect. During the preparation of the color particle slurry, dispersion treatment is required. If the strength of the color particles themselves is relatively low, they are prone to breakage during the dispersion process, which affects the three-dimensional effect of the glaze layer and even affects the clarity of the outline of the color particles in the glaze layer. In addition, if the organic binder is easily soluble in water, it will cause the color particles to dissolve during the preparation of the color particle slurry, thereby reducing the surface tension of the liquid in the slurry, causing a "split" phenomenon during the glazing process, leading to defects in the glazing process, such as the inability to form a complete glaze layer. The present application effectively improves the strength of the color particles by adding the above-mentioned specific types and amounts of organic binders to the color particles, ensuring that they are not prone to breakage during the dispersion process, ensuring that the glaze layer presents a significant three-dimensional effect, with clear outlines of the color particles and high-definition pattern textures, while avoiding the "split" phenomenon during the glazing process.
[0011] The weight ratio of the second transparent glaze to the inorganic color material needs to be controlled within the range of (15-75): (25-85), such as 15:85, 20:80, 30:70, 40:60, 50:50, 60:40, 70:30, 75:25 or an interval formed by any two of the above values.
[0012] The weight of the organic binder needs to be controlled to be 10% to 20% of the total weight of the second transparent glaze and the inorganic color material, such as 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or an interval formed by any two of the above values.
[0013] Preferably, the weight of the color particles is 0.5% to 15% of the total weight of the first transparent glaze and the water, such as 0.5%, 0.7%, 1%, 2%, 3%, 4%, 5%, 10%, 15% or an interval formed by any two of the above values.
[0014] When the weight of the color particles is 0.05% to 15% of the total weight of the first transparent glaze and the water, the three-dimensional effect and stain resistance of the glaze layer are better balanced.
[0015] Preferably, the weight of the water is 30% to 35% of the total weight of the first transparent glaze and the water, such as 30%, 31%, 32%, 33%, 34%, 35% or an interval formed by any two of the above values.
[0016] Preferably, the inorganic color material includes at least one of a ceramic color material and an opaque glaze. Among them, the ceramic color material can be selected from the ceramic color material commonly used in the art; the opaque glaze can also be the opaque glaze commonly used in the art. Exemplarily, the opaque glaze formed by the opaque glaze contains the following chemical components in weight percentage: 56% to 65% silicon dioxide, 20% to 25% aluminum oxide, 0.1% to 0.25% iron oxide, 0.1% to 0.25% titanium dioxide, 0.5% to 1.5% calcium oxide, 1% to 3% magnesium oxide, 0.5% to 2% potassium oxide, 2% to 5% sodium oxide, 3% to 6% zirconium oxide, 0.2% to 1% phosphorus pentoxide, and the rest is ignition reduction. The above-mentioned opaque glaze formula can make the color particles in the glaze layer appear white. Exemplarily, the opalescent glaze formed by the opalescent glaze contains the following chemical components in weight percentage: 55.5% silicon dioxide, 22.68% aluminum oxide, 0.13% iron oxide, 0.07% titanium dioxide, 3.05% calcium oxide, 0.21% magnesium oxide, 2.65% potassium oxide, 3.92% sodium oxide, 5.41% zirconium oxide, 0.21% phosphorus pentoxide, 3.05% zinc oxide, and the rest is loss on ignition.
[0017] When the inorganic color material is ceramic color powder, the weight ratio of the second transparent glaze material to the ceramic color powder is preferably (25~75):(25~75), such as 25:75, 30:70, 40:60, 50:50, 60:40, 70:30, 75:25 or an interval formed by any two of the above values, so as to better balance the three-dimensional effect and stain resistance of the glaze layer.
[0018] When the inorganic color material is an opalescent glaze, the weight ratio of the second transparent glaze to the opalescent glaze is preferably (15~50):(50~85), such as 15:85, 20:80, 30:70, 40:60, 50:50 or an interval formed by any two of the above values, so as to better balance the three-dimensional effect and stain resistance of the glaze layer.
[0019] Preferably, the mesh number of the color particles is 10-60 meshes, such as 10 meshes, 20 meshes, 30 meshes, 40 meshes, 50 meshes, 60 meshes or an interval formed by any two of the above values. When the mesh number of the color particles is within the range of 10-60 meshes, the ceramic product is ensured to have a flat surface after polishing, while the three-dimensional effect of the glaze layer is better.
[0020] The sizes of the color particles can be completely the same, partially different, or completely different. By grading color particles of different sizes, the color particle sizes are distributed in a layered manner, which will make the three-dimensional effect more natural and the visual effect better. For example, in some preferred embodiments, the color particles include first color particles, second color particles, and third color particles with increasing particle sizes, the particle size of the first color particles is 10 to 20 meshes, the particle size of the second color particles is 20 to 30 meshes, and the particle size of the third color particles is 30 to 60 meshes. The weight ratio of the first color particles, the second color particles, and the third color particles is (10 to 40): (20 to 60): (10 to 40), which makes the three-dimensional effect of the glaze layer more natural and the visual effect better.
[0021] The color of the color particles in the glaze layer formed by the color particle slurry is unlimited, and can be any color, such as white, yellow, gray, black, purple, blue, green, red, etc. Correspondingly, the color of the inorganic color material is also unlimited, and the corresponding inorganic color material can be selected according to the target color particles. In addition, the color particles in the glaze layer formed by the color particle slurry can be a single color or multiple colors, that is, a mixture of multiple color particles.
[0022] Preferably, the inorganic color material has two or more colors. When the inorganic color material has two or more colors, the color particles in the formed glaze layer are richer in color and more beautiful.
[0023] The first transparent glaze frit can adopt the transparent glaze frit commonly used in the art. Exemplarily, the transparent glaze formed by the first transparent glaze frit contains the following chemical components in weight percentage: 47-53% silicon dioxide, 13-17% aluminum oxide, 0.1-0.25% iron oxide, 0.1-0.2% titanium dioxide, 5-9% calcium oxide, 3-6% magnesium oxide, 1-4% potassium oxide, 2-5% sodium oxide, 1-3% barium oxide, 3-5% zinc oxide, and the rest is loss on ignition. Exemplarily, the transparent glaze formed by the first transparent glaze frit contains the following chemical components in weight percentage: 46% silicon dioxide, 18% aluminum oxide, 0.16% iron oxide, 0.11% titanium dioxide, 6.44% calcium oxide, 4.42% magnesium oxide, 5.21% potassium oxide, 2.52% sodium oxide, 4.24% barium oxide, 4.43% zinc oxide, and the rest is loss on ignition.
[0024] The second transparent glaze frit can adopt the transparent glaze frit commonly used in the art. Exemplarily, the transparent glaze formed by the second transparent glaze frit contains the following chemical components in weight percentage: 47-53% silicon dioxide, 13-17% aluminum oxide, 0.1-0.25% iron oxide, 0.1-0.2% titanium dioxide, 5-9% calcium oxide, 3-6% magnesium oxide, 1-4% potassium oxide, 2-5% sodium oxide, 1-3% barium oxide, 3-5% zinc oxide, and the rest is loss on ignition. Exemplarily, the transparent glaze formed by the first transparent glaze frit contains the following chemical components in weight percentage: 53% silicon dioxide, 13% aluminum oxide, 0.14% iron oxide, 0.15% titanium dioxide, 5.94% calcium oxide, 3.12% magnesium oxide, 2.53% potassium oxide, 2.50% sodium oxide, 4.12% barium oxide, 4.29% zinc oxide, and the rest is loss on ignition.
[0025] The first transparent glaze frit and the second transparent glaze frit may be the same or different.
[0026] The color particle slurry may further include additives such as a suspending agent, a water reducing agent, etc. Exemplarily, the suspending agent includes at least one of sodium carboxymethyl cellulose and polyvinyl alcohol; the water reducing agent includes at least one of sodium tripolyphosphate and sodium humate. Based on the total weight of the first transparent glaze and water, the amount of the suspending agent is 0.01-0.5 wt.%; the amount of the water reducing agent is 0.01-0.5 wt.%.
[0027] Preferably, the method for preparing the color particle slurry comprises the following steps:
[0028] The second transparent glaze material and the inorganic color material are mixed and dispersed, an organic binder is added and mixed, granulated, sieved, and dried to obtain color particles;
[0029] Mixing and dispersing the first transparent glaze material, water and additives to obtain an intermediate slurry;
[0030] The obtained color particles are added to the obtained intermediate slurry and dispersed to obtain a color particle slurry.
[0031] Preferably, in the above preparation method, the obtained color particles are 10-60 meshes, so as to ensure that the ceramic product has a flat surface after polishing and at the same time make the three-dimensional effect of the glaze layer better.
[0032] In the above preparation method, the size of the obtained color particles can be completely the same, partially different, or completely different. In some embodiments, color particles of different sizes are obtained by screening and graded so that the size of the color particles is distributed in a layered manner, which will make the three-dimensional effect more natural and the visual effect better. For example, in some preferred embodiments of the above preparation method, the obtained color particles include first color particles, second color particles, and third color particles with increasing particle sizes, wherein the particle size of the first color particles is 10-20 meshes, the particle size of the second color particles is 20-30 meshes, and the particle size of the third color particles is 30-60 meshes, and the weight ratio of the first color particles, the second color particles, and the third color particles is (10-40): (20-60): (10-40), which makes the three-dimensional effect of the glaze layer more natural and the visual effect better.
[0033] Preferably, in the process of preparing the color particles, the drying temperature after screening is 60-100° C., and the drying time after screening is 2-3 hours.
[0034] Preferably, the residue of the intermediate slurry passing through a 325-mesh sieve is ≤1wt.%, such as 1wt.%, 0.9wt.%, 0.8wt.%, 0.7wt.%, 0.6wt.%, 0.5wt.%, 0.4wt.%, 0.3wt.%, 0.2wt.%, 0.1wt.%, 0 or an interval formed by any two of the above values.
[0035] Preferably, in the process of preparing the color particle slurry using the color particles, the dispersion method is stirring, the stirring speed is 1000~6000rpm, and the stirring time is 0.5~5min.
[0036] In a second aspect, the present application provides a ceramic tile comprising a body layer, a base glaze layer and a glaze layer formed by the color particle slurry stacked in sequence.
[0037] In a third aspect, the present application provides a method for preparing ceramic tiles, comprising the following steps: performing a first drying after pressing the brick blank, applying a base glaze, pouring the color particle slurry in a bell-shaped glaze pouring manner, and then performing a second drying, firing, polishing, and edge grinding to obtain ceramic tiles.
[0038] Preferably, the sintering temperature is 1130-1175° C., and the sintering time is 35-55 min.
[0039] Preferably, the amount of the color particle slurry applied is 100-1000 g / cm 2 , the glaze slurry flow rate is 35~65s.
[0040] Preferably, the temperature of the second drying is 150-250°C.
[0041] Preferably, the first drying temperature is 150-160°C.
[0042] The present application has no limitation on the brick blanks, and ceramic brick blanks commonly used in the art may be used, especially ceramic brick blanks commonly used in the art.
[0043] The present application has no limitation on the base glaze, and the ceramic base glaze commonly used in the art may be used, especially the ceramic tile base glaze commonly used in the art.
[0044] Compared with the prior art, the beneficial effect of the present application is that the present application forms color particles according to a specific proportion of the second transparent glaze, inorganic color material and specific organic binder, and then combines the obtained color particles with the first transparent glaze and water to form a color particle slurry. The obtained color particle slurry can achieve a natural three-dimensional decorative effect on the ceramic surface, and the pattern texture is clear, and the "split" problem is not prone to occur during the glazing process. The obtained ceramic product has good stain resistance. Compared with inkjet printing, the outline of the color particles is more three-dimensional and clear, and the color is full and pure. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a process flow chart of the preparation of ceramic tiles in Example 1;
[0046] Figure 2 This is a photo of the process of pouring the color particle slurry in Comparative Example 7;
[0047] Figure 3 This is a photo of the process of pouring the color particle slurry in Example 1;
[0048] Figure 4 This is the surface effect diagram of the ceramic tile of Example 13;
[0049] Figure 5 This is a schematic diagram of the structure of the ceramic tile of Example 13. DETAILED DESCRIPTION
[0050] In order to better illustrate the purpose, technical solutions and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application are all commonly used ordinary reagents and instruments unless otherwise specified. In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0051] Example 1
[0052] This embodiment provides a method for preparing a ceramic tile, comprising the following steps:
[0053] The bricks are pressed, dried for the first time at 155°C, coated with base glaze, coated with color particle slurry in a bell-shaped glaze coating method, dried for the second time at 150°C, fired at 1150°C for 45 minutes, polished, and edged to obtain ceramic tiles;
[0054] Wherein, the preparation method of color particle slurry is as follows:
[0055] The second transparent glaze dry powder and the blue ceramic color powder are mixed and dispersed in a weight ratio of 50:50, and 15 wt.% of the total weight of the second transparent glaze dry powder and the blue ceramic color powder as an organic binder dimethyl silicone oil are added and mixed, granulated, sieved to obtain 10-20 mesh, 20-30 mesh, and 30-60 mesh particles, dried at 60° C. for 3 h, and the particles are graded in a weight ratio of 10-20 mesh: 20-30 mesh: 30-60 mesh = 10:60:30 to obtain blue particles;
[0056] The first transparent glaze dry powder and water are mixed and dispersed in a weight ratio of 70:30, and then 0.15% of sodium carboxymethyl cellulose and 0.3% of sodium tripolyphosphate are added to the total weight of the first transparent glaze dry powder and water, respectively, and dispersed to obtain an intermediate slurry;
[0057] Add 15 wt.% of blue particles to the intermediate slurry, and stir at 1000 rpm for 5 min to obtain a color particle slurry;
[0058] Among them, the first transparent glaze dry powder is the same as the second transparent glaze dry powder, and the formed transparent glaze contains the following chemical components in percentage by weight: 50% silicon dioxide, 15% aluminum oxide, 0.15% iron oxide, 0.15% titanium dioxide, 7% calcium oxide, 5% magnesium oxide, 2% potassium oxide, 4% sodium oxide, 2% barium oxide, 4% zinc oxide, and the rest is loss on ignition.
[0059] Example 2
[0060] This embodiment provides a method for preparing a ceramic tile, which is different from Embodiment 1 in that the weight ratio of the second transparent glaze dry powder to the blue ceramic color powder is 75:25.
[0061] Example 3
[0062] This embodiment provides a method for preparing a ceramic tile, which is different from Embodiment 1 in that the weight ratio of the second transparent glaze dry powder to the blue ceramic color powder is 25:75.
[0063] Example 4
[0064] This embodiment provides a method for preparing a ceramic tile, which is different from the embodiment 1 in that white particles are prepared instead of blue particles. The specific preparation method of the white particles is as follows:
[0065] The second transparent glaze dry powder and the opalescent glaze dry powder are mixed and dispersed in a weight ratio of 15:85, the second transparent glaze dry powder and the organic binder dimethyl silicone oil of 15% of the total weight of the opalescent glaze are added and mixed, granulated, sieved to obtain 10-20 mesh, 20-30 mesh, 30-60 mesh particles, dried at 60° C. for 3 h, and the particles are graded in a weight ratio of 10-20 mesh: 20-30 mesh: 30-60 mesh = 40:50:10 to obtain white particles, wherein the opalescent glaze dry powder contains the following chemical components in weight percentage: 60% silicon dioxide, 22% aluminum oxide, 0.15% iron oxide, 0.15% titanium dioxide, 1% calcium oxide, 2% magnesium oxide, 1.2% potassium oxide, 3% sodium oxide, 4% zirconium oxide, 0.6% phosphorus pentoxide, and the rest is loss on ignition;
[0066] The method for preparing color particle slurry using white particles is the same as that in Example 1.
[0067] Example 5
[0068] This embodiment provides a method for preparing a ceramic tile, which is different from Embodiment 4 in that the weight ratio of the second transparent glaze dry powder to the opalescent glaze dry powder is 30:70.
[0069] Example 6
[0070] This embodiment provides a method for preparing a ceramic tile, which is different from Embodiment 4 in that the weight ratio of the second transparent glaze dry powder to the opalescent glaze dry powder is 50:50.
[0071] Example 7
[0072] This embodiment provides a method for preparing a ceramic tile, which is different from Embodiment 1 in that the amount of dimethyl silicone oil as an organic binder added is 10 wt.% of the total weight of the second transparent glaze dry powder and the blue ceramic color powder.
[0073] Example 8
[0074] This embodiment provides a method for preparing a ceramic tile, which is different from Embodiment 1 in that the amount of dimethyl silicone oil as an organic binder added is 20 wt.% of the total weight of the second transparent glaze dry powder and the blue ceramic color powder.
[0075] Example 9
[0076] This embodiment provides a method for preparing a ceramic tile, which is different from Embodiment 1 in that the organic binder is isoamyl acetate.
[0077] Example 10
[0078] This embodiment provides a method for preparing a ceramic tile, which is different from Embodiment 1 in that the organic binder is methyl benzoate.
[0079] Embodiment 11
[0080] This embodiment provides a method for preparing ceramic tiles, which is different from Embodiment 1 in that the amount of blue particles added is 0.5 wt % of the weight of the intermediate slurry.
[0081] Example 12
[0082] This embodiment provides a method for preparing ceramic tiles, which is different from Embodiment 1 in that the amount of blue particles added is 10 wt % of the weight of the intermediate slurry.
[0083] Embodiment 13
[0084] This embodiment provides a method for preparing a ceramic tile, which is different from the embodiment 1 in that three kinds of color particles are prepared, namely black particles, white particles and orange particles, wherein the preparation methods of the black and orange particles are the same as the preparation method of the blue particles in the embodiment 1; the preparation method of the white particles is the same as that of the embodiment 4;
[0085] In this embodiment, in the process of preparing color particle slurry using intermediate slurry, black particles, white particles and orange particles are added to the intermediate slurry, and the weight ratio of black particles, white particles and orange particles is 5:4:1, and the sum of the added amounts of all color particles is 10wt.% of the weight of the intermediate slurry.
[0086] Embodiment 14
[0087] This embodiment provides a method for preparing ceramic tiles, which is different from Embodiment 1 in that, during the preparation of blue particles, particles of 20 to 30 mesh are screened and are not graded after drying to obtain target blue particles.
[0088] Embodiment 15
[0089] This embodiment provides a method for preparing a ceramic tile, which is different from Embodiment 1 in that the first transparent glaze dry powder and the second transparent glaze dry powder are different, wherein the first transparent glaze dry powder contains the following chemical components in percentage by weight: 47% silicon dioxide, 17% aluminum oxide, 0.25% iron oxide, 0.2% titanium dioxide, 9% calcium oxide, 6% magnesium oxide, 4% potassium oxide, 5% sodium oxide, 3% barium oxide, 5% zinc oxide, and the rest is loss on ignition;
[0090] The second transparent glaze glaze dry powder contains the following chemical components in percentage by weight: silicon dioxide 53%, aluminum oxide 13%, iron oxide 0.1%, titanium dioxide 0.1%, calcium oxide 5%, magnesium oxide 3%, potassium oxide 1%, sodium oxide 2%, barium oxide 1%, zinc oxide 3%, and the rest is loss on ignition.
[0091] Example 16
[0092] This embodiment provides a method for preparing a ceramic tile, which is different from Embodiment 1 in that the first transparent glaze dry powder and the second transparent glaze dry powder are different, wherein the first transparent glaze dry powder contains the following chemical components in percentage by weight: 53% silicon dioxide, 13% aluminum oxide, 0.1% iron oxide, 0.1% titanium dioxide, 5% calcium oxide, 3% magnesium oxide, 1% potassium oxide, 2% sodium oxide, 1% barium oxide, 3% zinc oxide, and the rest is loss on ignition;
[0093] The second transparent glaze dry powder contains the following chemical components in percentage by weight: silicon dioxide 47%, aluminum oxide 17%, iron oxide 0.25%, titanium dioxide 0.2%, calcium oxide 9%, magnesium oxide 6%, potassium oxide 4%, sodium oxide 5%, barium oxide 3%, zinc oxide 5%, and the rest is loss on ignition.
[0094] Comparative Example 1
[0095] This embodiment provides a method for preparing a ceramic tile, which is different from Embodiment 1 in that the weight ratio of the second transparent glaze dry powder to the blue ceramic color powder is 10:90.
[0096] Comparative Example 2
[0097] This embodiment provides a method for preparing a ceramic tile, which is different from Embodiment 1 in that the weight ratio of the second transparent glaze dry powder to the blue ceramic color powder is 80:20.
[0098] Comparative Example 3
[0099] This embodiment provides a method for preparing a ceramic tile, which is different from Embodiment 1 in that the weight ratio of the second transparent glaze dry powder to the opalescent glaze dry powder is 10:90.
[0100] Comparative Example 4
[0101] This embodiment provides a method for preparing a ceramic tile, which is different from Embodiment 1 in that the weight ratio of the second transparent glaze dry powder to the opalescent glaze dry powder is 80:20.
[0102] Comparative Example 5
[0103] This embodiment provides a method for preparing a ceramic tile, which is different from Embodiment 1 in that the addition amount of the organic binder dimethyl silicone oil is 7% of the total weight of the second transparent glaze dry powder and the blue ceramic color powder.
[0104] Comparative Example 6
[0105] This embodiment provides a method for preparing a ceramic tile, which is different from Embodiment 1 in that the amount of dimethyl silicone oil, an organic binder, added is 23% of the total weight of the second transparent glaze dry powder and the blue ceramic color powder.
[0106] Comparative Example 7
[0107] This embodiment provides a method for preparing a ceramic tile, which is different from Embodiment 1 in that the organic binder is glycerol.
[0108] Comparative Example 8
[0109] This embodiment provides a method for preparing a ceramic tile, which is different from Embodiment 1 in that the organic binder is ethyl acetate.
[0110] Observe whether "splits" occur in the above-mentioned embodiments and comparative examples during the pouring of color particle slurry, and perform the following performance tests on the obtained ceramic tiles:
[0111] Three-dimensional effect: The same experimenter conducted the test to determine the three-dimensional effect of the glaze particles from various angles;
[0112] Pollution resistance: GB / T 3810.14-2016 "Test methods for ceramic tiles Part 14: Determination of pollution resistance" is used to test the pollution resistance level;
[0113] If "splits" occur during the process of pouring the color particle slurry, the glaze on the surface of the ceramic tile will be defective and the material will have major defects, and there is no need to evaluate the three-dimensional effect and pollution resistance of the ceramic tile.
[0114] The test results are shown in Table 1.
[0115] Table 1
[0116]
[0117] It can be seen from the above data that in each embodiment of the present application, no "split" occurs during the process of pouring the color particle slurry, and the resulting ceramic tiles have significant three-dimensional effects and good stain resistance.
[0118] The ceramic tiles obtained in Comparative Examples 1 and 3 have a deviation in stain resistance. This is because the weight ratio of the second transparent glaze dry powder to the inorganic color material in the color particles is relatively low, resulting in a deviation in the adaptability of the color particles to the first transparent glaze, and the structural density of the area where the color particles are located in the glaze layer is relatively low; the ceramic tiles obtained in Comparative Examples 2 and 4 have a deviation in three-dimensional effect. This is because the weight ratio of the second transparent glaze dry powder to the inorganic color material in the color particles is relatively high, resulting in chemical corrosion of the inorganic color material, and the size of the color particles in the glaze layer cannot be well preserved.
[0119] In Comparative Example 5, the amount of organic binder used is too small, resulting in weak color particles. During the slurry making process, they are easily broken by stirring, resulting in a deviation in the three-dimensional effect of the ceramic tile. In Comparative Example 6, the amount of organic binder used is too large, resulting in a low surface tension of the color particle slurry liquid, which is prone to "split" during the glazing process, resulting in glaze defects on the surface of the ceramic tile and major defects in the material, so there is no need to talk about three-dimensional effect and pollution resistance.
[0120] Comparative Examples 7 and 8 use other organic binders, which results in splitting during the glazing process and more defects on the glaze surface before firing.
[0121] Figure 2 and Figure 3 It can be seen that when dimethyl silicone oil is used as the organic binder, no "split" phenomenon occurs during the glazing process, while when glycerol is used as the organic binder, the "split" phenomenon occurs during the glazing process.
[0122] Figure 4 and Figure 5 It can be seen that the surface of the ceramic tile obtained in Example 13 has a significant three-dimensional effect.
[0123] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A color particle slurry, characterized in that: Contains first clear glaze, color particles and water; The color particles include a second transparent glaze, an inorganic color material and an organic binder, wherein the weight ratio of the second transparent glaze to the inorganic color material is (15~75):(25~85), the weight of the organic binder is 10%~20% of the total weight of the second transparent glaze and the inorganic color material, and the organic binder includes at least one of dimethyl silicone oil, isopentyl acetate, and methyl benzoate.
2. The color particle slurry according to claim 1, characterized in that: The weight of the color particles is 0.5% to 15% of the total weight of the first transparent glaze material and the water; and / or The weight of the water is 30% to 35% of the total weight of the first transparent glaze and the water.
3. The color particle slurry according to claim 1, characterized in that: The inorganic color material includes at least one of a ceramic color material and an opacifying glaze material.
4. The color particle slurry according to claim 3, characterized in that: The inorganic color material is a ceramic color material, and the weight ratio of the second transparent glaze material to the ceramic color material is (25-75): (25-75); or The inorganic color material is an opaque glaze, and the weight ratio of the second transparent glaze to the opaque glaze is (15-50): (50-85).
5. The color particle slurry according to claim 3, characterized in that: The opaque glaze formed by the opaque glaze glaze contains the following chemical components in percentage by weight: 56% to 65% silicon dioxide, 20% to 25% aluminum oxide, 0.1% to 0.25% iron oxide, 0.1% to 0.25% titanium dioxide, 0.5% to 1.5% calcium oxide, 1% to 3% magnesium oxide, 0.5% to 2% potassium oxide, 2% to 5% sodium oxide, 3% to 6% zirconium oxide, 0.2% to 1% phosphorus pentoxide, and the rest is loss on ignition.
6. The color particle slurry according to claim 1, characterized in that: The mesh size of the color particles is 10 to 60 meshes.
7. The color particle slurry according to claim 1, characterized in that: At least one of the following conditions is met: (1) The color particles include first color particles, second color particles and third color particles with increasing particle sizes, the particle size of the first color particles is 10-20 meshes, the particle size of the second color particles is 20-30 meshes, the particle size of the third color particles is 30-60 meshes, and the weight ratio of the first color particles, the second color particles and the third color particles is (10-40): (20-60): (10-40); (2) The inorganic color material has two or more colors; (3) The transparent glaze formed by the first transparent glaze frit and the second transparent glaze frit each independently contains the following chemical components in percentage by weight: silicon dioxide 47%-53%, aluminum oxide 13%-17%, iron oxide 0.1%-0.25%, titanium dioxide 0.1%-0.2%, calcium oxide 5%-9%, magnesium oxide 3%-6%, potassium oxide 1%-4%, sodium oxide 2%-5%, barium oxide 1%-3%, zinc oxide 3%-5%, and the rest is loss on ignition.
8. A ceramic tile, characterized in that: It comprises a body layer, a base glaze layer and a glaze layer formed by the color particle slurry as described in any one of claims 1 to 7 which are stacked in sequence.
9. The method for preparing a ceramic tile according to claim 8, characterized in that: The following steps are involved: After the bricks are pressed, they are dried for the first time, the base glaze is applied, and the color particle slurry as described in any one of claims 1 to 7 is poured in a bell-shaped glaze pouring method, and then dried for the second time, fired, polished, and edged to obtain ceramic tiles.
10. The method for preparing a ceramic tile according to claim 9, characterized in that: At least one of the following conditions is met: S1. The firing temperature is 1130~1175°C, and the firing time is 35~55min; S2. The glaze amount of the color particle slurry is 100~1000g / cm 2 , glaze slurry flow rate is 35~65 s; S2. The temperature of the second drying is 150-250°C.
Citation Information
Patent Citations
Interference pigments on the basis of perlite flakes
CN102245715A
Color-mixed glaze of Jun porcelain and glaze applying method
CN107572788A